7,8-dihydroxyflavone enhances long-term spatial memory and alters brain volume in wildtype mice - Rawlings-Mortimer, Florence; Lazari, Alberto; Tisca, Cristiana; Tachrount, Mohamed; Martins-Bach, Aurea B.; Miller, Karla L.; Lerch, Jason P.; Johansen-Berg, Heidi (Frontiers in Systems Neuroscience, 2023)
7,8-dihydroxyflavone (7,8-DHF) is a low molecular weight compound that can cross the blood brain barrier and has been implicated in numerous functions and behaviours. It is thought to have neuroprotective capability and has been shown to alleviate symptoms in a wide range of diseases. Here we investigated the effect of systemic administration of 7,8-DHF on long-term memory in the Morris water maze in wildtype mice. Ex-vivo T2-weighted (T2w) was undertaken on a subset of these mice to assess for brain-wide changes in structure. We found that systemic 7,8-DHF administration during the training period enhanced spatial memory 28 days later. Volumetric changes were observed in numerous brain regions associated with a broad range of functions including cognition, sensory and motor processing. Our findings give the first whole brain overview of long-term anatomical changes following 7,8-DHF administration providing valuable information for assessing and understanding the widespread effects this drug has been shown to have in behaviour and disease.